New hybrid strains via intraspecific protoplast fusion of the entomopathogenic fungi Lecanicillium spp. - Liu, Liang; Liu, Chunlai; Yan, Lili; Yang, Fan; Wang, Shuang; Jiang, Xifeng; Li, Xinmin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The entomopathogenic fungal genus Lecanicillium Gams and Zare (formerly classified as the species Verticillium lecanii) includes species that are highly pathogenic to many insect genera. In this study, we identified six Lecanicillium spp. isolated strains (designated as V1-V6) belonging to L. lecanii (V1, V3 and V5) and L. attenuatum (V2, V4 and V6). In addition, these strains were used to obtain new strains via protoplast fusion, and nit mutants were used for protoplast selection. Genetic recombination of the hybrid strains was determined using the random amplified polymorphic DNA (RAPD) technique. We obtained nine stable fusant strains from 176 new hybrid strains, which were termed V12-10, V14-3, V16-4, V23-6, V25-8, V34-14, V36-5, V45-16 and V56-7. Morphological characteristics varied between the hybrid and parental strains. Genomic DNA analysis of the fusants also showed genetic recombination. The median lethal concentration (LC50) for the fusants were lower than that for parental strains, and the median survival time (LT50) for the fusants were reduced compared with that for parental strains. Thus, these results showed that we produced new, more virulent hybrid Lecanicillium spp. strains as biological control agents via intraspecific protoplast fusion.